PENGARUH GAYA KEPEMIMPINAN, SKILL DAN ATTITUDE TERHADAP KINERJA KARYAWAN (Studi pada karyawan Hotel Indah Palace di Tipes Surakarta) - Putri Ayu Adika; Ida Aryati; Istiqomah Istiqomah (ITB AAS INDONESIA Surakarta, 2020)
The Influence of Leadership Style, Skill, and Attitude on Employee Performance (Study of Indah Palace Hotel Employees in Tipes Surakarta). Thesis Management Study Program (S1). Surakarta Islamic Muslim University 2020. The purpose of this study wes to determine the effect of Leadership Style, Skill, and Attitude on Employee Performance (Study of Indah Palace Hotel Employees in Tipes Surakarta). This research uses quantitateve research. The population is all 40 employees of the Indah Palace Hotel Surakarta. The number of samples used was 40 respondents. The sampling technique uses non probability sampling method with saturated sampling approach. The data analysis technique used for this study is using multiple linear regression. The results of the study show that the F test influences the Leadership Style, Skill, and Attitude simultaneously and significantly influences the performance of employees at the Indah Place Hotel in Tipes Surakarta. T test results showed that the Leadership Style had a positive and significant effect on employee performance at the Indah Palace Hotel Surakarta, Skills had a positive and significant effect on employee performance at the Indah Palace Hotel Surakarta, and Attitude had a positive and significant effect on employee performance at the Indah Palace Hotel Surakarta. The coefficient of determination shows the variables of Leadership Style, Skill, and Attitude have an influence of 72,9% on the variable Employee Performance in the Indah Palace Hotel Surakarta, the rest of 27,1%. The most dominant influence on the performance of employees of the Indah Palace Hotel Surakarta is that the Leadership Style variable has the biggest t count, which is 4,287.